Agroforest diversity and ethnobotanical aspects in two villages of Berau, East Kalimantan, Indonesia - ADISTI PERMATASARI PUTRI HARTOYO; SUPRIYANTO SUPRIYANTO; ISKANDAR Z. SIREGAR; IDA THEILADE; LILIK B. PRASETYO (Society for Indonesian Biodiversity, 2018)
Hartoyo APP, Supriyanto, Siregar IZ, Theilade I, Prasetyo LB. 2018. Agroforest diversity and ethnobotanical aspects in two villages of Berau, East Kalimantan, Indonesia. Biodiversitas 19: 387-398. REDD+ aims to reduce emissions from deforestation and forest degradation, conservation, enhancement of forest carbon stocks, and sustainable forest management (SFM). An assessment of agroforest is important for REDD+ implementation in Indonesia. In this context, evaluation of the existing agroforests and their uses is an important issue. The objectives of this research were to characterize agroforest diversity with respect to habitat, regulation, production and information functions in Kampung Birang and Kampung Merabu, Berau, East Kalimantan. This research focused on two size classes of trees, namely medium trees (10?dbh?20 cm) and large trees (dbh>20 cm). Local community members were trained in plot establishment (60 plots, 50x50 m), tree diameter measurement, trees tagging, and herbarium collection. Local community members identified tree species by local names and listed the species uses. Results showed that agroforests as habitat obtained diversity indices (H’) of moderate category for Kampung Birang and high category for Kampung Merabu. Otherwise, Margalef’s index (Dmg) for the medium and large tree classes in Kampung Birang and Kampung Merabu were classified as high species richness category. This finding implies that enrichment planting using high economic value species is still necessary in Kampung Birang. Kampung Merabu was found to be more diverse than Kampung Birang, although soil quality in Kampung Birang was better than that in Kampung Merabu. Disturbances due to human activities that potentially impact agroforest stability were also pre-identified. The top ten tree species were classified based on importance value index (IVI) across both villages consisting of 80% shade intolerant and 20% semi-tolerant species. Agroforest showing production and information function as produces various edible fruits that are considered as key component for maintaining biodiversity sustainability and ecosystem functioning.